Sub 1-V highly-linear low-power class-AB bulk-driven tunable CMOS transconductor - Yodtean, A.; Thanachayanont, A. (My University, 2013)
This paper describes the design and realization of a sub 1-V low power class-AB bulk-driven tunable linear transconductor using a 0.18-μm CMOS technology. The proposed transconductor employs a class-AB bulk-driven differential input voltage follower and a passive resistor to achieve highly linear voltage-to-current conversion. Transconductance tuning is achieved by tuning the differential output current of the core transconductor with gain-adjustable current mirrors. With 10.4-μA current consumption from a 0.8-V single power supply voltage, simulation results show that the proposed transconductor achieves the total harmonic distortion (THD) of <-40 dB for a peak differential input voltage range of 800 mV at frequencies up to 10 kHz. The simulated input-referred noise voltage integrated over 10-kHz bandwidth is 100 μV, resulting to an input signal dynamic range of 75 dB for THD <-40 dB. A biquadratic Gm-C filter is designed to demonstrated the performance of the proposed transconductor. At the nominal 10-kHz cut-off frequency, the filter dissipates 34.4 μW from a 0.8-V supply voltage and it achieves an input signal dynamic range of 67.4 dB for the third-order intermodulation distortion of <-40 dB. © 2013 Springer Science+Business Media New York.
Keywords: Bulk-driven; Class-AB; Linear transconductor; Operational transconductance amplifier